Efficacy and safety of thread embedding acupuncture for facial expression muscles atrophy after peripheral facial paralysis: study protocol for a randomized controlled trial - Binyan Yu (BMC, 2021)
Abstract Background Facial expression muscles atrophy is one kind of sequelae after peripheral facial paralysis. It causes critical problems in facial appearance of patient as well as social and psychological problems. This study aims to evaluate the efficacy and safety of Thread-embedding acupuncture (TEA) for the management of facial expression muscles atrophy after peripheral facial paralysis. Methods This is a patient-assessor blinded, randomized, sham-controlled trial. A total of fifty-six eligible patients will be randomly divided into TEA (n=28) and sham TEA (STEA) (n=28) groups. Both groups will receive TEA or STEA treatment at the frontal muscle and the depressor anguli oris muscle, at one predefined points once a week for eight weeks. Additionally, both groups will receive traditional acupuncture treatment at ten acupoints (GB20, LI4, LR3, GB12, ST7, SI18, LI20, BL2, SJ23, ST4) twice a week for eight weeks as a concurrent treatment. B-mode ultrasonography will be used to assess the changes in facial expression muscle thickness ratio of the affected/healthy side at baseline and at 10 weeks after screening, as the primary outcome. House-Brackmann Grade and lip mobility score will be measured and analyzed at baseline and 4, 8, 10, and 12 weeks after screening, as secondary outcomes. Discussion The study will compare TEA with sham TEA to explore the feasibility for TEA in improving facial expression muscles atrophy after peripheral facial paralysis. Trial registration Chinese Clinical Trial Registry, ChiCTR1900027170. Registered on 3 November 2019, http://www.chictr.org.cn/edit.aspx?pid=45173&htm=4